1995
DOI: 10.1093/carcin/16.7.1623
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of K-ras mutations in lung neoplasms from female B6C3F1 mice exposed to ozone for 24 or 30 months

Abstract: The National Toxicology Program recently completed long-term ozone inhalation studies in B6C3F1 mice and F344/N rats. Mice and rats were exposed to 0, 0.5 or 1.0 p.p.m. ozone by inhalation for 24 or 30 months. There was an increased incidence of lung neoplasms in B6C3F1 mice. However, there was no evidence of carcinogenicity in F344/N rats. The objectives of this study were to (i) evaluate benign and malignant lung neoplasms from B6C3F1 mice for mutations in the K-ras gene at codons 12, 13 and 61, (ii) determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…In ADBAQ-induced lung tumors, A to T transversions (6/23, 26%) and A to G transitions (5/23, 22%) were identied in K-ras codon 61 ( Table 4). The K-ras codon 61 CTA mutation was considered to be chemical speci c since this mutation has not been detected previously in 82 spontaneous lung tumors of B6C3F 1 mice (7,11,25) or in lung tumors from concurrent control mice (Table 4). When K-ras mutation pro les were compared in lung tumors from mice exposed to 10,000 or 20,000 ppm ADBAQ, most of the codon 61 A T mutations were observed in the high dosage groups.…”
Section: Lung Tumorsmentioning
confidence: 99%
“…In ADBAQ-induced lung tumors, A to T transversions (6/23, 26%) and A to G transitions (5/23, 22%) were identied in K-ras codon 61 ( Table 4). The K-ras codon 61 CTA mutation was considered to be chemical speci c since this mutation has not been detected previously in 82 spontaneous lung tumors of B6C3F 1 mice (7,11,25) or in lung tumors from concurrent control mice (Table 4). When K-ras mutation pro les were compared in lung tumors from mice exposed to 10,000 or 20,000 ppm ADBAQ, most of the codon 61 A T mutations were observed in the high dosage groups.…”
Section: Lung Tumorsmentioning
confidence: 99%
“…Ozone caused lung tumors in mice, with a high frequency of K-ras mutations including G to T transversion in codon 12 (Sills et al, 1995). Alveolar type II cells in rat lungs exposed intratracheally to inorganic particles, resulting in neutrophil and macrophage in®ltration, showed a large increase in HPRT mutations (Driscoll et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Reports concerning rodents chronically exposed to 0, have reported an increase in lung tumors in some studies but not others [Werthamer et al, 1970;Last et al, 19871. One study has reported an 0,-induced increase in lung tumors when urethane was co-administered, suggesting O3 may act as a co-carcinogen [Hassett et al, 19851. Recent reports from the National Toxicology Program have shown that B6C3F1 mice, but not Fischer 344 rats, exposed to 1.0 ppm 0, for 24 or 30 months had an increase in lung neoplasms, suggesting the carcinogenicity of 0, exposure alone [Sills et al, 1995;Boorman et al, times, solution additives (e.g., metal chelators), fatty acid types, fatty acid concentrations, and/or different reaction mechanisms. For example, we utilized only 37°C in our exposures while others have reported using lower temperatures.…”
Section: Discussionmentioning
confidence: 99%